Problems in Business Statistics/Laboratory Handbook of Statistical Methods. - Fletcher, R. C. (The Accounting Review, 1932)
Reviews two books on accountancy. "Problems in Business Statistics," by Theodore H. Brown; "Laboratory Handbook of Statistical Methods," by T.H. Brown, B.F. Bingham and V.A. Temnomeroff.